Federalism and Subsidiarity : NOMOS LV - Levy, Jacob T., 1971-; Fleming, James E. (Book collections on Project MUSE., 2014)
"In Federalism and Subsidiarity, a distinguished interdisciplinary group of scholars in political science, law, and philosophy address the application and interaction of the concept of federalism within law and government. What are the best justifications for and conceptions of federalism? What are the most useful criteria for deciding what powers should be allocated to national governments and what powers reserved to state or provincial governments? What are the implications of the principle of subsidiarity for such questions? What should be the constitutional standing of cities in federations? Do we need to "remap" federalism to reckon with the emergence of translocal and transnational organizations with porous boundaries that are not reflected in traditional jurisdictional conceptions? Examining these questions and more, this latest installation in the NOMOS series sheds new light on the allocation of power within federations"--